Determinants of financial education in Ecuador - Meza Villacis, Arelis Patricia (2022)
Financial education influences the development of economic agents, providing efficient knowledge to manage their resources. This article will identify the level of financial literacy in Ecuador, through building a Financial Knowledge indicator based on sub-indicators, applying the structural equation methodology by the partial least squares method PLS-SEM. The results obtained are consistent and identified the provinces of Ecuador that have high or low levels of financial knowledge. In addition, a binomial logit model was used to characterize individuals’ socio-demographically. Demonstrated that being a woman and living in rural areas decreases the probability of having financial knowledge and that having a job, or some degree of formal education does not guarantee that individuals have a high level of financial literacy.